Set-Based Design of frame bridges - Development and implementation - Löfgren, Simon (My University, 2020)
ABSTRACT The traditional design process of bridges in structural engineering is based on the design approach called Point-Based design. To minimize environmental impact and industrialize the design process, the theory of Set-Based design (SBD) has been recognized as a promising approach. Since frame bridges is one of the most common bridge types in Sweden, the main objective of this thesis is to develop and implement a SBD tool for frame bridges. To be able to evaluate the different design alternatives generated by the design tool, evaluation criteria within buildability and sustainability are identified. Buildability is a concept within building industry that aims to improve productivity and safety within on-site production while also reducing the costs of the construction process. The building industry is one of the major contributors regarding impact on its surrounding. Therefore, there is a huge potential in improving the sustainability within the building industry. Sustainability is divided in Environment, Social and Economy aspects. The design tool allows performing an automated and iterative structural preliminary design of several frame bridge alternatives specified within ranges of design parameters. The design alternatives are analyzed with Finite Element Analysis (FEA) and evaluated according to predefined evaluation criteria. By scripting the design tool in programing language Python, it is possible to control an FEA program, such as Brigade Plus, from the design tool as well as performing a preliminary design of frame bridges. The preliminary design is performed according to requirements in national building codes, Eurocode. Finally, a case study is performed to investigate how a SBD tool can be implemented in an infrastructure project containing several frame bridges. In a large infrastructure project and with a SBD tool it is possible to find one optimum bridge solution that fulfills the need of several bridges in a set of bridges. The contractor can then industrialize parts of the construction of frame bridges, hopefully leading to a more sustainable and cost-effective building of frame bridges.
Keywords: Set-Based design; Repeatability; Frame bridges; Preliminary design; Finite Element Analysis; Buildability; Sustainability; Cost-efficiency